PELATIHAN BAHASA INGGRIS UNTUK POKDARWIS (KELOMPOK SADAR WISATA) KABUPATEN BANJAR, PROVINSI KALIMANTAN SELATAN - Sari, Erini Junita; Hanifah, Hanifah (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to enhance the English communication skills of members of the Tourism Awareness Group (Pokdarwis) in Banjar Regency, South Kalimantan. This program addressed the lack of English proficiency which hinders the ability of Pokdarwis members to provide quality services to foreign tourists. The method involved three-day training sessions combining interactive lectures, role plays, and direct practice in tourism scenarios. The results showed improved confidence and basic English usage among participants in greeting, giving directions, and explaining tourist attractions.